1994
DOI: 10.1111/j.1365-2141.1994.tb04903.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional analysis of bone marrow progenitor cell compartment in bone marrow failure

Abstract: Many laboratory findings have demonstrated that the haemopoietic stem cell compartment is defective in aplastic anaemia (AA). AA bone marrow (BM) and peripheral blood (PB) are profoundly deficient in colony-forming cells, and AA progenitors fail to proliferate in long-term assays even in the presence of an intact stroma. Our study was designed to characterize some quantitative and qualitative aspects of the progenitor cell defect in AA. Using flow cytometric analysis of BM from new AA patients and from those r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 15 publications
3
66
1
4
Order By: Relevance
“…5,30,31 As some cases of moderate AA 5,30,31 and lowgrade MDS (e.g., the 5qÀ syndrome 32,33 ) never progress to 34,35 whereas hypoplastic MDS patients generally have higher bone marrow CD34 þ cell counts. 9,10,36,37 However, significant overlap in the CD34 percentages between these two disorders has precluded using this assay diagnostically. 9,10,36,37 Technical issues and difficulty precisely diagnosing AA and hMDS may account for the differences between previous reports and our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,30,31 As some cases of moderate AA 5,30,31 and lowgrade MDS (e.g., the 5qÀ syndrome 32,33 ) never progress to 34,35 whereas hypoplastic MDS patients generally have higher bone marrow CD34 þ cell counts. 9,10,36,37 However, significant overlap in the CD34 percentages between these two disorders has precluded using this assay diagnostically. 9,10,36,37 Technical issues and difficulty precisely diagnosing AA and hMDS may account for the differences between previous reports and our findings.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,36,37 However, significant overlap in the CD34 percentages between these two disorders has precluded using this assay diagnostically. 9,10,36,37 Technical issues and difficulty precisely diagnosing AA and hMDS may account for the differences between previous reports and our findings. Low CD34 þ cell percentages seen in some hMDS patients in other studies may have been the result of contamination of bone marrow aspirates with peripheral blood, as there was no description of criteria for validating the quality of their marrow samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of CD34 cells is much reduced in aplastic anemia [ 13,141. Recently, it has been shown that there is a profound defecit in long-term initiating cells which have the frequency, phenotype and kinetic properties of true stem cells [15, 161. lost to follow-up [lo].…”
Section: Progenitor Cells In Aplastic Anemiamentioning
confidence: 99%